Pengaruh perubahan tarif pajak dan ukuran perusahaan terhadap struktur modal perusahaan manufaktur di Bursa Efek Indonesia pada tahun 2017-2019 - Fitria Sugma Sugestiara; Pujo Gunarso (Jurnal Ilmiah Bisnis dan Perpajakan (Bijak), 2021)
This study was conducted to examine the effect of the variable tax rate and firm size on the capital structure of manufacturing companies listed on the Indonesian stock exchange in 2017-2019. The sampling technique was purposive sampling and obtained a sample of 13 companies. Data analysis technique using multiple linear regression test. The results of the study partially show that the tax rate has no significant effect on the capital structure. While the size of the company has a significant effect on the capital structure.